Applying electric current to inactivate gram-negative bacteria isolated from salt-packed-cured hides - (:unkn) unknown (Society of Leather Technologists and Chemists, 2013)
Proteolytic and lipolytic bacteria on salt-pack cured hides may reduce leather quality by causing grain damage, looseness, chrome soaps, fatty spues, uneven dyeing, weakness and holes in leathers. To prevent bacterial damage on salt-pack cured hides during storage and other processes, the antibacterial effects of 1.5A alternating electric current on Enterobacter cloacae, Pseudomonas luteola and Vibrio fluvialis, as well as a mixed population of these micro-organisms isolated from the hides, were separately examined in brine solution containing 25% NaCl. Fifteen minutes exposure to 1.5A alternating current inactivated all of the test bacteria in the brine solution. Additionally, 1.5A alternating current for 15 minutes and followed by 1.5A direct current for 1 minute inactivated the mixed population of these bacteria in the brine solution. The maximum temperature rise was 6°C. This research proved that inactivation of harmful Gram-negative bacteria via 1.5A alternating electric current followed by 1.5A direct electric current, may be an effective method of bacterial inactivation with bacteria which are difficult to inactivate with chemical antibacterial agents because of their formidable permeability barrier. In conclusion, alternating electric current treatment applied together with direct electric current is a very effective method to inactivate a mixed culture of Gram-negative bacterial population in the brine curing process.